Rancang Bangun Sistem Kontrol Mini Manufacture Mesin Pencetak Kerupuk Basah Berbasis Programmable Logic Controller (PLC) Outsel - Budang, Sanju; Hasan, Hasan; Yuniarto, Wendhi (Jurusan Teknik Elektro Politeknik Negeri Pontianak, 2024)
The primary objective of this research is to develop a wet cracker printing machine that enhances efficiency and accuracy in the printing process. The research began with initial observations, literature studies, equipment design, calculations, programming, performance testing of the equipment and programming, data collection and analysis, and finally, conclusions. The automated wet cracker printing machine based on PLC Outseal was successfully created, utilizing an AC motor from a washing machine to grind and mix the dough within a mixing tube that also functions as a printing tube. The machine is equipped with a proximity sensor to detect the length of the dough, a pneumatic solenoid as a dough cutting knife, and a 12V DC gearbox motor to drive the conveyor, which moves the printed dough..